Measurement of the percentage of root filling in oval-shaped canals obturated with Thermafil Obturators and Beefill 2in1: In vitro study - Faus-Llácer, Vicente (J Clin Exp Dent, 2015)
BACKGROUND: The aim of the study was to measure the percentage of root canal fillings in long oval canals obturated with thermoplasticized gutta-percha techniques, Beefill 2in1® and Thermafil Obturators®. MATERIAL AND METHODS: Fifty four mandibular incisors were selected after bucco-lingual and mesio-distal radiographs showed at 5 mm from apex an internal long:short diameter ≥2. Teeth were instrumented with Protaper Universal and divided in two groups of 27. Group 1 was obturated with Thermafil Obturators® and group 2 with Beefill 2in1®. Two horizontal sections were cut at 5 and 7 mm from the apex and photographed in a stereo-microscope. The total area of the canal and filled canal in cross-sections were measured with AutoCad and the percentages of gutta-percha-sealer and voids in the canal were obtained. RESULTS: Both systems achieved high percentage of filled canal, Thermafil 96.8% and Beefill 2in1 98.9%. The percentages of voids in both groups were very low. No significant differences were found between the two groups . The percentage obtained at 5 and 7 mm from the apex in both groups showed no significant difference. CONCLUSIONS: The percentages of filled canal (gutta-percha-sealer) were high and these two thermoplasticized techniques are suitable for long oval canals obturation. Key words:Long oval canal, oval canal, thermoplasticized obturation.